Winning with people: discover the people principles that work for you everytime - "Maxwell, John C." (Ahmedabad, 2012)
Discover the people principles that work for you every time. If you can win with people, you can win. Many people focus on other talents and abilities first -such as polishing their communication or leadership skills or taking courses to expand their base of knowledge -but they forget that good relationships are the foundation for achievement. Winning with People will provide you with the tools you need to immediately improve your existing relationships as well as cultivate strong, exciting, new ones. Using a unique blend of interesting facts, statistics, humor, real-life examples and questions for discussion, Winning with People will show you how: The Skills You Use + The Relationships You Choose = Success.
Keywords: Interpersonal relations